2018
DOI: 10.1016/j.jgeb.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin A deficiency on thymosin-β4 and CD4 concentrations

Abstract: Vitamins are evaluated for their role in immunity. Recently, vitamin A received a particular attention as a critical micronutrient for regulating immune system. Therefore, the present study aimed to search for new about vitamin A. Forty-eight Egyptian adults aged from 18 to 42 years old from both sexes were subjected to clinical examination and nutrition questionnaire and were screened for vitamin A by using ELISA method. Forty subjects were selected and subdivided into two groups. Group 1 with vitamin A at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…They were divided into subclinical hypothyroidism (SH) group (TSH over 2.5 mU/l) and normal thyroid group depending on the TSH levels (8,22,23). VAD was defined as VA ≤ 200 ng/ml (24,25), marginal vitamin A deficiency (MVAD) was defined as VA > 200 ng/ml but <300 ng/ml, and vitamin A normal (NVA) was defined as VA ≥ 300 ng/ml. Among them, 244 obese subjects underwent LSG.…”
Section: Subjectsmentioning
confidence: 99%
“…They were divided into subclinical hypothyroidism (SH) group (TSH over 2.5 mU/l) and normal thyroid group depending on the TSH levels (8,22,23). VAD was defined as VA ≤ 200 ng/ml (24,25), marginal vitamin A deficiency (MVAD) was defined as VA > 200 ng/ml but <300 ng/ml, and vitamin A normal (NVA) was defined as VA ≥ 300 ng/ml. Among them, 244 obese subjects underwent LSG.…”
Section: Subjectsmentioning
confidence: 99%
“…In addition, there is a decrease in the function of macrophages, monocytes, and other immune cells like natural killer cells, and a decrease in the number and function of CD4+ T-lymphocytes , B lymphocyte cells and T helper 6,12,13 . Effective antibody response is also impaired by the number and dysfunction of antigen presenting B lymphocytes and T lymphocytes 6,14,15 . In HIV-infected patients, the CD4+ T cell population decreases gradually as disease progresses.…”
Section: Introductionmentioning
confidence: 99%
“…Thymosin-β4 (Tβ4) is the prevailing form, representing a proximately 80% of the total content of thymosin It is considered to play a significant role in the cellular metabolism due to its actin-sequestering properties. Thymosin-β4 mRNA has various expression in human immune cells suggesting a relationship between immune response and Tβ4 15,23 , and its initial purpose is to encourage the development of T lymphocytes, which are targets of thymosin activity 24 . In a study, a strongly positive correlation as found between VitA and both Tβ4 and CD4 at p <.000 and p.003, respectively 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin A is important for normal immune function, and vitamin A deficiency is associated with profound defects in adaptive immunity and thereby infections ( Green and Mellanby, 1928 ; El-Zayat et al, 2018 ). Hence, vitamin A has been described as “the anti-infective vitamin” ( Green and Mellanby, 1928 ; El-Zayat et al, 2018 ; Wilhelm et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%